PREDICTING RURAL STEM TEACHERS’ ACCEPTANCE OF MOBILE LEARNING IN THE FOURTH INDUSTRIAL REVOLUTION - David Mutambara; Anass Bayaga (Journal of Construction Project Management and Innovation)
In South Africa, high schools’ Science, Technology, Engineering, and Mathematics (STEM) education is faced with many challenges. However, previous studies have shown that mobile learning (m-learning) can be used to lessen the challenges faced in STEM education. Despite the benefits that m-learning can bring into STEM classrooms, its adoption is still below the expected rate. The acceptance of m-learning depends on the attitude of its users. Most studies focused on learners’ acceptance of m-learning. However, very little is known about rural high school STEM teachers’ acceptance of m-learning in the Fourth industrial revolution (4IR) era. This study proposes a model, which extends the Technology Acceptance Model by introducing perceived social influence and perceived resources. Stratified random sampling was used to select 150 teachers to participate in the survey. A total of 114 valid questionnaires were collected, and data were analysed using partial least squares structural equation modelling. The proposed model explained 37.9 % of the variance in teachers’ behavioural intention to use m-learning in the 4IR era. Perceived attitude towards the use was found to be the best predictor of teachers’ behavioural intention, followed by perceived ease of use, perceived resources, perceived social influence, and lastly perceived usefulness.